First record of characterization C-KIT mutation in buccal swab DNA of piebaldism suspect balo from balo community, Pujananting South Sulawesi - Muthiadin, Cut; Arisuryanti, Tuty; Aziz, Isna Rasdianah; Hajrah, Hajrah; Khatimah, Khusnul; Hidayat, Muhammad Tasri (Tropical Genetics, 2024)
ABSTRACT Piebaldism is a disorder in the area of ​​the body caused by an autosomal genetic predominance of the development of melanocytes.The method used in this study is a qualitative method which aims to determine the variation of the KIT-c gene present in the To Balo mucosa samples.The results of this study indicate thatThe change is caused by a point mutation process where in patients with piabeldism the nucleotide bases of sequence 1391 and 1392 undergo changes, where the normal nucleotide base adenine (A) changes to cytosine (C) and cytosine (C) changes to adenine (A). So it can be concluded that the To Balo community in Bulo-Bulo village, Pujananting District, Barru Regency, South Sulawesi suffers from an autosomal dominant hereditary disease or piebaldism.